Pole piece, roll core and battery

CN122968244APending Publication Date: 2026-10-23JIANGSU RELIANCE ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611233585.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

该区域曲率半径小、应力集中,极片抗膨胀能力弱,电解液回流路径长且极易闭合,导致高倍率极化加剧与循环析锂

Benefits of technology

本发明提供了一种极片,极片用于卷绕形成卷芯,极片含有硅基活性物质,极片沿自身长度方向的一端具有卷首区域,卷首区域位于卷芯的内圈,卷首区域沿自身厚度方向贯通开设有通孔,通孔沿极片的长度方向的尺寸A11满足:d50×s≤A11≤1000μm,通孔沿极片的宽度方向的尺寸A12满足:d50×s≤A12≤1000μm,其中,d50为硅基活性物质颗粒的平均直径,s%为极片的硅基活性物质的质量占比。该极片通过在卷首区域开设通孔,会重构应力场并提供自由变形空间,即可实现膨胀应力的主动释放,从而提高极片的抗膨胀能力。并且通过限定通孔的尺寸,即限定通孔的尺寸大于等于d50与s的乘积,且由于s一般大于等于8,即极片的硅基活性物质的质量占比一般会大于等于8%,因此通孔的尺寸大于等于8倍的硅基活性物质颗粒的平均直径,即可防止硅基活性物质颗粒膨胀后堵塞通孔。通孔侧壁处也可能会膨胀挤占通孔内的空间,而这种膨胀现象会因为硅基活性物质的质量占比的提高而越发显著,因此限定通孔的尺寸大于等于d50与s的乘积,即可保证通孔不会封堵上,从而可供电解液流经,缩短电解液的回流路径。因此,该极片可降低高倍率充放电下的极化效应,抑制负极析锂现象,提高循环稳定性与使用安全性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968244A_ABST
    Figure CN122968244A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of energy storage devices, and particularly relates to a pole piece, a roll core and a battery. The pole piece is used for winding to form a roll core. The pole piece contains a silicon-based active material. The pole piece has a winding head region at one end along the length direction of the pole piece. The winding head region is located at the inner ring of the roll core. The winding head region is provided with a through hole along the thickness direction of the winding head region. The size A11 of the through hole along the length direction of the pole piece satisfies: d 50 xs <= A11 <= 1000 mu m. The size A12 of the through hole along the width direction of the pole piece satisfies: d 50 xs <= A12 <= 1000 mu m. d 50 is the average diameter of the silicon-based active material particles, and s% is the mass percentage of the silicon-based active material in the pole piece. The roll core comprises the pole piece. The battery comprises a shell and the roll core. The roll core is arranged in the shell. The pole piece, the roll core and the battery have higher anti-expansion capability, can reduce the polarization effect under high-rate charging and discharging, inhibit the lithium precipitation phenomenon of the negative electrode, and improve the cycle stability and use safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of energy storage equipment technology, and in particular to an electrode, a core, and a battery. Background Technology

[0002] With the increasing demand for high-energy-density lithium-ion cylindrical batteries, the areal density and compaction density of electrodes are continuously increasing. To compensate for energy density loss, high-silicon materials are often introduced into the negative electrode. However, silicon expands dramatically during lithium insertion / extraction, with an expansion rate exceeding 20%. The stress generated by this expansion, combined with the residual stress from high compaction, makes the inner ring of the core (i.e., the roll head region) a high-incidence area for electrolyte reflux stagnation and interfacial side reactions. This region has a small radius of curvature, concentrated stress, weak electrode expansion resistance, and a long, easily closed electrolyte reflux path, leading to intensified high-rate polarization and lithium plating during cycling. Summary of the Invention

[0003] One objective of this invention is to provide an electrode that can help improve the electrode's resistance to expansion, shorten the electrolyte's reflux path, reduce the polarization effect under high-rate charge and discharge, suppress lithium plating on the negative electrode, and improve the battery's cycle stability and safety.

[0004] To achieve this objective, the present invention adopts the following technical solution: An electrode sheet is provided for winding to form a core. The electrode sheet contains a silicon-based active material. One end of the electrode sheet along its length direction has a winding head region located on the inner ring of the core. A through hole is formed in the winding head region along its thickness direction. The dimension A11 of the through hole along the length direction of the electrode sheet satisfies: d 50 ×s≤A11≤1000μm, the dimension A12 of the through hole along the width direction of the electrode sheet satisfies: d 50 ×s≤A12≤1000μm, where d 50 s% represents the average diameter of the silicon-based active material particles, and s% represents the mass percentage of the silicon-based active material in the electrode.

[0005] Optionally, the electrode sheet has a rolled-tail region at its other end along its length direction. The rolled-tail region is located on the outer ring of the core, and a blind hole is formed in the rolled-tail region along its thickness direction.

[0006] Optionally, the dimension A21 of the blind hole along the length direction of the electrode sheet satisfies d 50 ×s≤A21≤1000μm, the dimension A22 of the blind hole along the width direction of the electrode sheet satisfies, d 50 ×s≤A22≤1000μm, where d 50 s% represents the average diameter of the silicon-based active material particles, and s% represents the mass percentage of the silicon-based active material in the electrode.

[0007] Optionally, blind holes are provided on both sides of the rolling tail region, and the depth D1 of the blind hole on one side along the thickness direction of the electrode and the thickness D of the electrode satisfy: 0.1≤D1 / D≤0.3.

[0008] Optionally, the dimension of the roll-up region along the length direction of the electrode is L1, and the overall length of the electrode is L, satisfying: 0.15≤L1 / L≤0.3; And / or, the tail region is connected to the head region.

[0009] Optionally, a plurality of through holes are provided in the beginning area, with any two through holes spaced apart; and a plurality of blind holes are provided in the end area, with any two blind holes spaced apart. The distance between the centers of two adjacent through holes along the length direction of the electrode is S1, and the distance between the centers of two adjacent blind holes along the length direction of the electrode is S3, satisfying: S3 / S1≥1+0.05s, where s% is the mass percentage of the silicon-based active material of the electrode; and / or, The distance between the centers of two adjacent through holes along the width direction of the electrode is S2, and the distance between the centers of two adjacent blind holes along the width direction of the electrode is S4, satisfying: S2=S4.

[0010] Optionally, a plurality of through holes are provided in the head area, and any two through holes are spaced apart; The distance between the centers of two adjacent through holes along the length of the electrode is S1, satisfying: 0.1mm ≤ S1 ≤ 2mm; and / or, The distance between the centers of two adjacent through holes along the width direction of the electrode is S2, satisfying: 0.1mm ≤ S2 ≤ 2mm; and / or, The through hole is a circular hole, and the diameter A1 of the through hole satisfies: 80μm≤A1≤600μm.

[0011] Optionally, a plurality of blind holes are provided in the rolled-tail area, and any two blind holes are spaced apart; The distance between the centers of two adjacent blind holes along the length of the electrode is S3, satisfying: 0.14mm ≤ S3 ≤ 4mm; and / or, The distance between the centers of two adjacent blind holes along the width direction of the electrode is S4, satisfying: 0.1mm ≤ S4 ≤ 2mm; and / or, The blind hole is a circular hole, and the diameter A2 of the blind hole satisfies: 80μm≤A2≤600μm.

[0012] Another objective of this invention is to provide a winding core with higher resistance to expansion, which can reduce the polarization effect under high-rate charge and discharge, suppress lithium plating on the negative electrode, and improve cycle stability and safety of use.

[0013] To achieve this objective, the present invention adopts the following technical solution: A winding core is provided, comprising the aforementioned electrode sheet.

[0014] Another objective of this invention is to provide a battery in which the core has higher resistance to expansion, can reduce polarization under high-rate charge and discharge, suppress lithium plating at the negative electrode, and improve cycle stability and safety.

[0015] To achieve this objective, the present invention adopts the following technical solution: A battery is provided, including a housing and the aforementioned winding core, the winding core being disposed within the housing.

[0016] The beneficial effects of this invention are: This invention provides an electrode sheet for winding into a core. The electrode sheet contains a silicon-based active material. One end of the electrode sheet along its length direction has a roll head region located on the inner ring of the core. A through hole is formed in the roll head region along its thickness direction. The dimension A11 of the through hole along the length direction of the electrode sheet satisfies: d 50 ×s≤A11≤1000μm, the dimension A12 of the through hole along the width direction of the electrode sheet satisfies: d 50 ×s≤A12≤1000μm, where d 50 d represents the average diameter of the silicon-based active material particles, and s% represents the mass percentage of the silicon-based active material in the electrode. This electrode, by creating through-holes in the roll-up region, reconstructs the stress field and provides free deformation space, thus achieving active release of expansion stress and improving the electrode's resistance to expansion. Furthermore, by limiting the size of the through-holes, specifically ensuring the size is greater than or equal to d... 50 The product of d and s, and since s is generally greater than or equal to 8, meaning the mass percentage of silicon-based active material in the electrode is generally greater than or equal to 8%, the size of the via must be greater than or equal to 8 times the average diameter of the silicon-based active material particles to prevent the silicon-based active material particles from expanding and clogging the via. The sidewalls of the via may also expand and encroach on the space within the via, and this expansion phenomenon becomes more significant as the mass percentage of silicon-based active material increases. Therefore, the size of the via is limited to be greater than or equal to d. 50 The product of this and 's' ensures that the through-hole will not be blocked, allowing the electrolyte to flow through and shortening the electrolyte's return path. Therefore, this electrode can reduce the polarization effect under high-rate charge and discharge, suppress lithium plating on the negative electrode, and improve cycle stability and safety.

[0017] The present invention also provides a wound core comprising the aforementioned electrode sheet. This wound core exhibits higher resistance to expansion, reduces polarization effects under high-rate charge-discharge conditions, suppresses lithium plating on the negative electrode, and improves cycle stability and safety.

[0018] The present invention also provides a battery comprising a casing and the aforementioned winding core, wherein the winding core is disposed within the casing. The winding core of this battery exhibits higher resistance to expansion, reduces polarization effects under high-rate charge-discharge conditions, suppresses lithium plating at the negative electrode, and improves cycle stability and safety in use. Attached Figure Description

[0019] Figure 1 This is a schematic diagram of the electrode structure provided in an embodiment of the present invention; Figure 2 This is a partial cross-sectional view of the electrode sheet provided in an embodiment of the present invention.

[0020] In the picture: 100. Electrode; 110. Beginning area; 111. Through hole; 120. End area; 121. Blind hole; 101. First active material layer; 102. Current collector; 103. Second active material layer. Detailed Implementation

[0021] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and not intended to limit it. Furthermore, it should be noted that, for ease of description, only the parts relevant to the present invention are shown in the accompanying drawings, not all of them.

[0022] In the description of this invention, it should be noted that, unless otherwise explicitly specified and limited, the terms "installation," "connection," and "linking" should be interpreted broadly. For example, they can refer to fixed connections or detachable connections; mechanical connections or electrical connections; direct connections or indirect connections through an intermediate medium; and internal connections between two components. Those skilled in the art can understand the specific meaning of these terms in this invention based on the specific circumstances.

[0023] In this invention, unless otherwise explicitly specified and limited, "above" or "below" the second feature can include direct contact between the first and second features, or contact between the first and second features through another feature between them. Furthermore, "above," "over," and "on top" of the second feature includes the first feature directly above or diagonally above the second feature, or simply indicates that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature includes the first feature directly below or diagonally below the second feature, or simply indicates that the first feature is at a lower horizontal level than the second feature.

[0024] With the increasing demand for high-energy-density lithium-ion cylindrical batteries, the areal density and compaction density of electrodes are continuously increasing. To compensate for energy density loss, high-silicon materials are often introduced into the negative electrode. However, silicon expands dramatically during lithium insertion / extraction, with an expansion rate exceeding 20%. The stress generated by this expansion, combined with the residual stress from high compaction, makes the inner ring of the core (i.e., the roll head region) a high-incidence area for electrolyte reflux stagnation and interfacial side reactions. This region has a small radius of curvature, concentrated stress, weak electrode expansion resistance, and a long, easily closed electrolyte reflux path, leading to intensified high-rate polarization and lithium plating during cycling.

[0025] Therefore, this embodiment provides an electrode 100 to solve the above problems. The electrode 100 can help improve the anti-expansion ability of the electrode 100, shorten the electrolyte reflux path, reduce the polarization effect under high rate charge and discharge, suppress the negative electrode lithium plating phenomenon, and improve the cycle stability and safety of the battery.

[0026] like Figures 1-2 As shown, the electrode 100 in this embodiment is used to wind a core. The electrode 100 contains a silicon-based active material. One end of the electrode 100 along its length direction has a winding head region 110, which is located in the inner circle of the core. The winding head region 110 has a through hole 111 extending through it along its thickness direction. The dimension A11 of the through hole 111 along the length direction of the electrode 100 satisfies: d 50 ×s≤A11≤1000μm, the dimension A12 of the through hole 111 along the width direction of the electrode 100 satisfies: d 50 ×s≤A12≤1000μm, where d 50 denoted as the average diameter of the silicon-based active material particles, and s% as the mass percentage of the silicon-based active material in electrode 100.

[0027] The electrode 100, by creating a through-hole 111 in the roll-up region 110, reconstructs the stress field and provides free deformation space, thereby actively releasing expansion stress and improving the electrode 100's resistance to expansion. Furthermore, by limiting the size of the through-hole 111, specifically by ensuring that the size of the through-hole 111 is greater than or equal to d... 50The product of d and s, and since s is generally greater than or equal to 8, meaning the mass percentage of silicon-based active material in electrode 100 is generally greater than or equal to 8%, the size of via 111 is greater than or equal to 8 times the average diameter of the silicon-based active material particles. This prevents the silicon-based active material particles from expanding and clogging the via 111. The sidewalls of via 111 may also expand and encroach on the space within the via 111. This expansion phenomenon becomes more significant as the mass percentage of silicon-based active material increases. Therefore, the size of via 111 is limited to be greater than or equal to d. 50 The product of s and s ensures that the through hole 111 will not be blocked, allowing the electrolyte to flow through and shortening the electrolyte return path. Therefore, this electrode 100 can reduce the polarization effect under high-rate charge and discharge, suppress lithium plating on the negative electrode, and improve cycle stability and safety.

[0028] Optionally, in this embodiment, the average diameter d of the silicon-based active material particles is... 50 The value range is 5μm-20μm. The mass percentage (s%) of the silicon-based active material in electrode 100 ranges from 8% to 20%. Therefore, d 50 The product of s and s ranges from 40μm to 600μm. The dimensions A11 of the through hole 111 along the length of the electrode 100 and A12 along the width of the electrode 100 must both be greater than or equal to 40μm.

[0029] If the dimensions A11 of the through hole 111 along the length direction of the electrode 100 and A12 along the width direction of the electrode 100 are less than d 50 If the product of the via and s is greater than 1000 μm, the via 111 may be blocked during the lithium insertion / extraction expansion of the silicon-based active material, thus losing its function of supplying electrolyte flow. If the dimensions A11 of the via 111 along the length direction of the electrode 100 and A12 along the width direction of the electrode 100 are greater than 1000 μm, then the size of the via 111 is too large, which will affect the structural strength of the roll-up region 110 and is also not conducive to its adaptation to expansion stress.

[0030] Optionally, the electrode 100 has a rolled-tail region 120 at the other end along its length direction. The rolled-tail region 120 is located on the outer ring of the core. The rolled-tail region 120 has blind holes 121 along its thickness direction, which can improve the electrolyte wettability of the rolled-tail region 120 and absorb expansion stress to a certain extent. In addition, the rolled-tail region 120 of the electrode 100 does not have through holes 111, which can improve wettability while taking into account the structural strength of the core.

[0031] Optionally, the dimension A21 of the blind hole 121 along the length direction of the electrode 100 satisfies d 50 ×s≤A21≤1000μm, the dimension A22 of the blind hole 121 along the width direction of the electrode 100 satisfies, d 50×s≤A22≤1000μm, where d 50 s% represents the average diameter of the silicon-based active material particles, and s% represents the mass percentage of the silicon-based active material in the electrode 100. Optionally, the dimensions A21 of the blind via 121 along the length direction of the electrode 100 and A22 along the width direction of the electrode 100 must both be greater than or equal to 40 μm.

[0032] If the dimensions A21 of the blind hole 121 along the length direction of the electrode 100 and A22 along the width direction of the electrode 100 are less than d 50 If the product of the two is s, the blind hole 121 may be blocked during the lithium insertion / extraction expansion of the silicon-based active material, thus losing its function of improving wettability. If the dimensions A21 of the blind hole 121 along the length direction of the electrode 100 and the dimensions A22 along the width direction of the electrode 100 are greater than 1000 μm, then the size of the blind hole 121 is too large, which will affect the mass density and structural strength of the roll head region 110.

[0033] Optionally, blind holes 121 are provided on both opposite sides of the rolled-up tail region 120, that is, blind holes 121 are provided on both the inner and outer rings, which can improve the absorption effect of expansion stress. Furthermore, since the rolled-up tail region 120 is a low-stress region, it is not necessary to provide through holes 111 to absorb stress. Optionally, the blind holes 121 on opposite sides of the rolled-up tail region 120 are arranged opposite to each other or staggered.

[0034] Optionally, the depth D1 of the blind hole 121 along the thickness direction of the electrode 100 and the thickness D of the electrode 100 satisfy the following: 0.1 ≤ D1 / D ≤ 0.3. If the ratio of the depth D1 of the blind hole 121 along the thickness direction of the electrode 100 to the thickness D of the electrode 100 is less than 0.1, the blind hole 121 is too shallow, and its effect on absorbing stress and improving wettability is not significant. If the ratio of the depth D1 of the blind hole 121 along the thickness direction of the electrode 100 to the thickness D of the electrode 100 is greater than 0.3, although the effect of absorbing stress and improving wettability can be guaranteed, the core capacity loss is too great.

[0035] Optionally, the dimension of the roll-up region 110 along the length of the electrode 100 is L1, and the overall length of the electrode 100 is L, satisfying: 0.15 ≤ L1 / L ≤ 0.3. This ratio of the roll-up region 110 allows the high-conductivity area to accurately cover the high-stress zone of the inner ring of the core. If the ratio of the dimension L1 of the roll-up region 110 along the length of the electrode 100 to the overall length L of the electrode 100 is less than 0.15, some areas will still be high-expansion-stress areas, but without through-holes 111 to absorb stress, these areas will still experience a lower degree of electrolyte reflux stagnation and interfacial side reactions. If the ratio of the dimension L1 of the roll-up region 110 along the length of the electrode 100 to the overall length L of the electrode 100 is greater than 0.3, through-holes 111 will be opened in areas with low stress, causing unnecessary capacity loss and compromising the structural strength of the core.

[0036] Optionally, the tail region 120 is connected to the head region 110, that is, the dimension of the tail region 120 along the length direction of the electrode 100 is L2 = L - L1.

[0037] Optionally, the beginning area 110 is provided with multiple through holes 111, with any two through holes 111 spaced apart, and the end area 120 is provided with multiple blind holes 121, with any two blind holes 121 spaced apart.

[0038] like Figure 2 As shown, the distance between the centers of two adjacent through holes 111 along the length of the electrode 100 is S1, and the distance between the centers of two adjacent blind holes 121 along the length of the electrode 100 is S3, satisfying: S3 / S1≥1+0.05s, where s% is the mass percentage of silicon-based active material in the electrode 100. When s is at its minimum value of 8, S3 / S1≥1.4. When the size of the through hole 111 is constant, the distance S1 between the centers of two adjacent through holes 111 along the length of the electrode 100 cannot be too large, that is, the density of through holes 111 needs to be sufficiently high to ensure stress absorption effect and electrolyte reflux efficiency. When S1 is constant, S3 needs to be greater than 1.4 times S1, and the higher the mass percentage of silicon-based active material, the greater the difference between S3 and S1. This is because the core is wound and formed along the length of the electrode 100. If S3 is too small, the blind holes 121 will be set too densely, which will cause insufficient tensile strength of the electrode 100. In addition, if S3 is too small, it will also affect the peel strength of the material area, which will increase the probability of powder shedding and coating peeling of the electrode 100 during rolling, slitting and other processes. In subsequent charge and discharge cycles, the active material is more likely to detach from the current collector 102, which will increase the internal resistance of the battery, accelerate the capacity decay, and even increase the probability of safety hazards such as internal short circuit.

[0039] It is known that when S3 is constant, the higher the mass ratio of silicon-based active material, the greater the expansion effect of the roll head region 110. Therefore, the roll head region 110 needs to ensure that the density of the through holes 111 is large enough to improve the stress absorption effect.

[0040] Optionally, in this embodiment, the distance between the centers of two adjacent through holes 111 along the width direction of the electrode 100 is S2, and the distance between the centers of two adjacent blind holes 121 along the width direction of the electrode 100 is S4, satisfying: S2=S4.

[0041] Optionally, the distance between the centers of two adjacent through holes 111 along the length of the electrode 100 is S1, satisfying: 0.1mm ≤ S1 ≤ 2mm. If the distance S1 between the centers of two adjacent through holes 111 along the length of the electrode 100 is less than 0.1mm, the through holes 111 are set too densely, making processing too difficult and increasing the proportion of defects, which is not conducive to ensuring the yield of the electrode 100. If the distance S1 between the centers of two adjacent through holes 111 along the length of the electrode 100 is greater than 2mm, the through holes 111 are set too sparsely, which will lead to poor stress absorption effect in the roll-up region 110 and low electrolyte reflux efficiency.

[0042] Optionally, the distance S1 between the centers of two adjacent through holes 111 along the length of the electrode 100 is 0.1mm, 0.2mm, 0.3mm, 0.4mm, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm, 1.1mm, 1.2mm, 1.3mm, 1.4mm, 1.5mm, 1.6mm, 1.7mm, 1.8mm, 1.9mm, or 2mm.

[0043] Optionally, the distance between the centers of two adjacent through holes 111 along the width direction of the electrode 100 is S2, satisfying: 0.1mm ≤ S2 ≤ 2mm. If the distance S2 between the centers of two adjacent through holes 111 along the width direction of the electrode 100 is less than 0.1mm, the through holes 111 are set too densely, making processing too difficult and increasing the proportion of defects, which is not conducive to ensuring the yield of the electrode 100. If the distance S2 between the centers of two adjacent through holes 111 along the width direction of the electrode 100 is greater than 2mm, the density of through holes 111 is too sparse, which will lead to poor stress absorption effect in the roll-up region 110 and low electrolyte reflux efficiency.

[0044] Optionally, the distance S2 between the centers of two adjacent through holes 111 along the width direction of the electrode 100 is 0.1mm, 0.2mm, 0.3mm, 0.4mm, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm, 1.1mm, 1.2mm, 1.3mm, 1.4mm, 1.5mm, 1.6mm, 1.7mm, 1.8mm, 1.9mm, or 2mm.

[0045] Optionally, in this embodiment, the through-hole 111 is a circular hole, i.e., A11=A12=A1, where A1 is the pore diameter of the through-hole 111, and A1 satisfies: 80μm≤A1≤600μm. If the pore diameter A1 of the through-hole 111 is less than 80μm, then when the average diameter d of the silicon-based active material particles... 50 When the particle size is large, silicon-based active material particles easily block the through-hole 111, obstructing the electrolyte return path. When the mass percentage of silicon-based active material in the electrode 100 is high (s%), the expansion deformation will be greater, also easily causing the through-hole 111 to become blocked. Furthermore, if the through-hole 111 is too small, it cannot accommodate large expansion stress, meaning the stress absorption effect of the through-hole 111 is also poor. If the aperture A1 of the through-hole 111 is greater than 600 μm, the capacity loss of the core will be higher, and the structural strength reduction of the winding head region 110 will also be greater.

[0046] Preferably, the pore size A1 of the through hole 111 is in the range of 100μm-200μm, which can be adapted to the average diameter d of the silicon-based active material particles. 50 When the mass percentage of silicon-based active material in both electrode 100 and electrode 100 is moderate, the capacity loss of the core can be minimized while ensuring the structural strength of the winding head area 110, provided that stress absorption and electrolyte recirculation are met.

[0047] Optionally, the aperture A1 of the through hole 111 is 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 180μm, 190μm or 200μm.

[0048] Optionally, the distance between the centers of two adjacent blind holes 121 along the length of the electrode 100 is S3, satisfying: 0.14mm ≤ S3 ≤ 4mm. If the distance S3 between the centers of two adjacent blind holes 121 along the length of the electrode 100 is less than 0.14mm, the blind holes 121 are set too densely, which is not conducive to ensuring the tensile strength and material peel strength of the winding tail area 120, thereby reducing the yield of the core. If the distance S3 between the centers of two adjacent blind holes 121 along the length of the electrode 100 is greater than 4mm, the density of blind holes 121 is too sparse, which will lead to poor stress absorption effect in the winding tail area 120 and limited improvement in wettability.

[0049] Optionally, the distance S3 between the centers of two adjacent blind holes 121 along the length direction of the electrode 100 is 0.14mm, 0.2mm, 0.3mm, 0.4mm, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm, 1.1mm, 1.2mm, 1.3mm, 1.4mm, 1.5mm, 1.6mm, 1.7mm, 1.8mm, 1.9mm, 2mm, 2.1mm, 2.2mm, 2.3mm, 2.4mm, 2.5mm, 2.6mm, 2.7mm, 2.8mm, 2.9mm, 3mm, 3.1mm, 3.2mm, 3.3mm, 3.4mm, 3.5mm, 3.6mm, 3.7mm, 3.8mm, 3.9mm, or 4mm.

[0050] Optionally, the distance between the centers of two adjacent blind holes 121 along the width direction of the electrode 100 is S4, satisfying: 0.1mm ≤ S4 ≤ 2mm. If the distance S4 between the centers of two adjacent blind holes 121 along the width direction of the electrode 100 is less than 0.1mm, the blind holes 121 are set too densely, making processing too difficult and increasing the proportion of defects, which is not conducive to ensuring the yield of the electrode 100. If the distance S4 between the centers of two adjacent blind holes 121 along the width direction of the electrode 100 is greater than 2mm, the density of blind holes 121 is too sparse, which will lead to poor stress absorption effect in the rolled-up area 120 and limit the improvement of wettability.

[0051] Optionally, the distance S4 between the centers of two adjacent blind holes 121 along the width direction of the electrode 100 is 0.1mm, 0.2mm, 0.3mm, 0.4mm, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm, 1.1mm, 1.2mm, 1.3mm, 1.4mm, 1.5mm, 1.6mm, 1.7mm, 1.8mm, 1.9mm, or 2mm.

[0052] Optionally, the blind via 121 is a circular via, and the pore diameter A2 of the blind via 121 satisfies: 80μm≤A2≤600μm. If the pore diameter A2 of the blind via 121 is less than 80μm, then when the average diameter d of the silicon-based active material particles... 50 When the diameter is large, the silicon-based active material particles can easily block the blind via 121, obstructing the wetting path of the electrolyte within the blind via 121. If the blind via 121 is too small, its stress absorption effect will be poor. If the aperture A2 of the blind via 121 is greater than 600 μm, the capacity loss of the core will be high, and the structural strength of the roll tail region 120 will also decrease significantly, which is not conducive to ensuring the tensile strength and peel strength of the electrode 100.

[0053] Preferably, the pore size A2 of the blind aperture 121 is in the range of 100μm-200μm, which can be adapted to the average diameter d of the silicon-based active material particles. 50 When the mass percentage (s%) of silicon-based active material in electrode 100 is moderate, the capacity loss of the core can be minimized while ensuring the structural strength of the core, provided that stress absorption and electrolyte reflux are met.

[0054] Optionally, the aperture A2 of the blind aperture 121 is 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 180μm, 190μm or 200μm.

[0055] Using the aforementioned electrode 100 as the negative electrode, a 21700 cylindrical lithium-ion battery was assembled, and its performance was tested. The battery assembly method is as follows: After rolling, the electrode 100 was first slit and baked to remove moisture, and then the positive and negative electrode 100 and the separator were wound into a cylindrical core. After the core was placed in the casing, laser welding was performed on the bottom and the cap, followed by vacuum liquid injection and sealing. After liquid injection, the battery needed to be placed in a dry environment for pre-charge film formation and formation. After formation, the battery was sent to an aging chamber for high-temperature aging to stabilize the electrochemical interface and screen for products with abnormal self-discharge. After aging, constant current discharge capacity testing was performed, and the batteries were sorted and screened according to capacity and internal resistance. Finally, qualified battery products were obtained, with a rated capacity of 5000mAh (the positive electrode was conventional and not specially treated).

[0056] To verify whether the electrode 100 provided in this embodiment has stronger anti-expansion performance, whether it can shorten the electrolyte reflux path, reduce the polarization effect under high-rate charge and discharge, and suppress lithium plating on the negative electrode, this embodiment provides a series of experimental verification data. As shown in Table 1 below, this embodiment provides two sets of examples and thirteen sets of comparative examples. A series of tests were conducted on the electrode 100 and batteries of the two sets of examples and thirteen sets of comparative examples. The test results are recorded in Table 2 below. The test methods are described below: (1) Test method for porosity of electrode 100: The porosity of the negative electrode is determined by the gas displacement method, specifically by the following steps: The negative electrode is immersed in ethyl methyl carbonate (EMC) for cleaning, and then measured by the gas displacement method. The porosity of the negative electrode is the percentage of the pore volume in the negative electrode to the total volume of the negative electrode. The calculation formula is: Porosity = (V-V0) / V×100%, where V0 is the true volume of the negative electrode and V is the apparent volume of the negative electrode.

[0057] (2) Test method for peel strength of material area: Cut an electrode 100 sample with a width of 25 mm and a length of 150 mm. Apply high-strength double-sided adhesive tape to the surface of the material area (coating side) and attach it to a clean stainless steel test plate. Roll the sample three times at a uniform speed using a 1 kg roller to ensure uniform adhesion. At room temperature, fix the test plate to the tensile tester fixture and peel the current collector 102 at a constant speed of 100 mm / min along a 180° direction. Record the peel force and displacement data to obtain the peel force-displacement curve. Take the average peel force of the stable segment of the curve and divide it by the sample width to calculate the peel strength of the material area (N / m). This value is used to quantitatively characterize the adhesion between the active material layer and the current collector 102.

[0058] (3) Test method for battery capacity and 10C discharge capacity retention: Install the battery on the Arbin test cabinet fixture with a range of 60A, and connect the voltage and current lines to the temperature sampling line. Set the capacity test program in a constant temperature environment, with a cutoff voltage range of 2.5V-4.2V. After discharging to 1A, perform a full charge at 2.5A constant current and constant voltage, and then discharge at 1A with a rest time of 30 minutes. Repeat the above charging steps, and then discharge at 50A with a rest time of 30 minutes. Record the discharge capacity value after full charge. The battery capacity is the 1A discharge capacity. The battery 10C discharge capacity retention rate = 50A discharge capacity / 1A discharge capacity.

[0059] (4) Test method for capacity retention after 500 cycles: Install the battery on the Arbin battery test cabinet fixture with a range of 60A, and connect the voltage and current lines to the temperature sampling line. Set the cycle test program in a constant temperature environment, with a cutoff voltage range of 2.5V-4.2V, a charging current of 15A, a discharging current of 40A, and a rest time of 30min. Capacity retention after 500 cycles = Discharge capacity after the first cycle / Discharge capacity after the 500th cycle.

[0060] Table 1 Table 2 In Comparative Examples 12 and 13, the electrode 100 did not have through holes 111 or blind holes 121. Compared with Comparative Examples 12 and 13, these two examples, with the same battery capacity, showed higher porosity in the electrode 100, resulting in improved kinetic performance and cycle performance. Taking Example 1 and Comparative Example 12 as examples, compared to the former, the battery in Example 1 showed an approximately 17% improvement in 10C rate discharge capacity retention and a 9% improvement in capacity retention after 500 cycles. This demonstrates that having through holes 111 and blind holes 121 on the electrode 100 can improve the battery's kinetic performance and cycle performance.

[0061] The diameter of the through hole 111 in the electrode 100 of both Comparative Example 1 and Comparative Example 2 is smaller than d. 50 The product of d and s, i.e., the pore size of through hole 111, is too small. Compared to Examples 1 and 2, the porosity of Comparative Examples 1 and 2 is reduced, resulting in a worse rate discharge capability of the battery and poor resistance to expansion during cycling. Furthermore, electrolyte reflux is again obstructed in the later stages of cycling, thus reducing the cycle capacity retention rate. It can be seen that the pore size of through hole 111 in the rolled-up region 110 of electrode 100 is greater than or equal to d. 50 The product of s and s helps to improve the battery's rate discharge capability and its resistance to expansion, resulting in improved cycle capacity retention and better long-term battery performance.

[0062] In Comparative Example 3, the aperture of the through-hole 111 in the electrode 100 is greater than 1000 μm, meaning the aperture of the through-hole 111 is too large. This significantly reduces the material peel strength of the electrode 100, and the capacity retention rate after 500 cycles is also lower. This is because material shedding, expansion, and even detachment of the conductive network are more likely to occur during cycling, all of which accelerate the capacity decay of the battery. Furthermore, the large aperture of the through-hole 111 also contributes to some capacity loss. Therefore, when the aperture of the through-hole 111 in the electrode 100 is less than or equal to 1000 μm, it is more beneficial to improve the battery capacity in the initial state and to ensure the material peel strength, thus preventing battery capacity decay.

[0063] The diameter of the blind hole 121 in the electrode 100 of Comparative Example 4 and Comparative Example 5 is smaller than d. 50 The product of d and s indicates that the diameter of the through hole 111 is too small. Compared to Examples 1 and 2, the porosity of the electrode 100 in Comparative Examples 4 and 5 is reduced, resulting in a worse rate discharge capability of the battery. Furthermore, the anti-expansion capability at the blind hole 121 is weaker during cycling, leading to a decrease in cycle capacity retention. It can be seen that the diameter of the blind hole 121 in the rolled-up region 120 of the electrode 100 is greater than or equal to d. 50 The product of s and s is beneficial to improving the battery's rate discharge capability and helps to enhance its resistance to expansion, resulting in improved cycle capacity retention and better long-term battery performance.

[0064] In Comparative Example 6, the blind via 121 of electrode 100 has a diameter greater than 1000 μm, meaning the diameter of blind via 121 is too large. This significantly reduces the material peel strength of electrode 100 and results in a lower capacity retention rate after 500 cycles. This is because material shedding, expansion, and even conductive network detachment are more likely to occur during cycling, all of which accelerate battery capacity decay. Furthermore, the large diameter of blind via 121 also contributes to some capacity loss. Therefore, a blind via 121 diameter of electrode 100 of less than or equal to 1000 μm is more beneficial for improving the battery capacity in its initial state and for ensuring material peel strength, thus preventing battery capacity decay.

[0065] In Comparative Example 7, the D1 / D value of electrode 100 is less than 0.1, which is less than the minimum value in the optimal range. In this case, the etching depth of blind via 121 is too small. Consequently, the improvement in electrolyte reflux and battery kinetic performance is limited, and the improvement in cycle performance is not significant. Therefore, when the D1 / D value of electrode 100 is greater than or equal to 0.1, and the depth of blind via 121 is sufficient, the battery made with electrode 100 shows better improvement in electrolyte reflux and kinetic performance, and a significant improvement in cycle performance.

[0066] In Comparative Example 8, the D1 / D value of electrode 100 is greater than 0.3, which is greater than the maximum value in the optimal range. In this case, the etching depth of blind via 121 is too deep. Although the porosity of electrode 100 is significantly improved, compared to Examples 1 and 2, the material peel strength and cycle capacity retention of electrode 100 in Comparative Example 8 are both reduced. It is evident that when the D1 / D value of electrode 100 is less than or equal to 0.3, and the depth of blind via 121 is appropriate, the battery made from electrode 100 shows better improvement in electrolyte reflux and kinetic performance, and a significant improvement in cycle performance.

[0067] In Comparative Example 9, the L1 / L value of electrode 100 is less than 0.15, which is less than the minimum value in the optimal range. This indicates that the coverage area of ​​through-hole 111 is too small. Although the material area peel strength of electrode 100 in Comparative Example 9 is high, the 10C rate discharge capacity retention rate and the capacity retention rate after 500 cycles are not significantly improved compared to the comparative example without through-hole 111 and blind hole 121. This means the improvement effect on electrolyte reflux and battery kinetic performance is limited, and the improvement in cycle performance is not significant. Therefore, when the L1 / L value of electrode 100 is greater than or equal to 0.15, and the coverage area of ​​through-hole 111 is sufficiently long, the battery made with electrode 100 will show better improvement in electrolyte reflux and kinetic performance, and a significant improvement in cycle performance.

[0068] In Comparative Example 10, the L1 / L value of electrode 100 is greater than 0.3, which is greater than the maximum value in the optimal range. This indicates that the coverage area of ​​through-hole 111 is too large. Although the porosity of electrode 100 is significantly improved, the material area peel strength and cycle capacity retention of electrode 100 are significantly lower compared to Examples 1 and 2. Compared to Comparative Example 13, the 10C rate discharge capacity retention of the battery in Comparative Example 10 is significantly improved, but the capacity retention after 500 cycles is not significantly improved. Therefore, when the L1 / L value of electrode 100 is less than or equal to 0.3, and the length of the coverage area of ​​through-hole 111 is appropriate, the cycle performance of the battery made from electrode 100 is significantly improved.

[0069] In Comparative Example 11, the S3 / S1 ratio of electrode 100 is less than 1, which is less than the minimum value of 1.5 within the optimal range. This indicates that the distribution density of blind vias 121 is too high. Although the 10C rate discharge capacity retention of the battery is significantly improved, the material peeling strength of electrode 100 is reduced. During cycling, the detachment of the conductive network caused by material shedding and expansion will accelerate capacity decay. Therefore, the capacity retention of the battery in Comparative Example 11 after 500 cycles is not significantly improved compared to Comparative Example 13. It can be seen that when the S3 / S1 value of electrode 100 is greater than or equal to 1 + 0.05s, and the distribution density of blind vias 121 is appropriate, the cycle performance of the battery made from electrode 100 is significantly improved.

[0070] It can be seen that when the electrode 100 has through holes 111 and blind holes 121, and the diameter of the through hole 111 satisfies d 50 When ×s≤A1≤1000μm, the electrolyte reflux and kinetic performance of the battery made with electrode 100 are improved, and the cycle performance is also improved. When electrode 100 further satisfies the above-mentioned optimal value range, i.e., d... 50 When ×s≤A2≤1000μm, 0.1≤D1 / D≤0.3, 0.15≤L1 / L≤0.3, and S3 / S1≥1+0.05s, the battery made of electrode 100 shows significant improvement in electrolyte reflux and kinetic performance, as well as significant improvement in cycle performance.

[0071] This embodiment also provides a winding core, including the aforementioned electrode 100. This winding core has higher resistance to expansion, can reduce polarization effects under high-rate charge / discharge, suppress lithium plating on the negative electrode, and improve cycle stability and safety.

[0072] This embodiment also provides a battery, including a casing and the aforementioned winding core, with the winding core disposed within the casing. The winding core of this battery has higher resistance to expansion, can reduce polarization effects under high-rate charge and discharge, suppress lithium plating at the negative electrode, and improve cycle stability and safety.

[0073] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. An electrode, characterized in that, The electrode (100) is used to wind a core. The electrode (100) contains a silicon-based active material. One end of the electrode (100) along its length direction has a head region (110). The head region (110) is located in the inner circle of the core. The head region (110) has a through hole (111) extending through it along its thickness direction. The dimension A11 of the through hole (111) along the length direction of the electrode (100) satisfies: d 50 ×s≤A11≤1000μm, the dimension A12 of the through hole (111) along the width direction of the electrode (100) satisfies: d 50 ×s≤A12≤1000μm, where d 50 s% is the average diameter of the silicon-based active material particles, and s% is the mass percentage of the silicon-based active material in the electrode (100).

2. The electrode sheet according to claim 1, characterized in that, The electrode (100) has a rolled-tail region (120) at the other end along its length direction. The rolled-tail region (120) is located on the outer ring of the core. The rolled-tail region (120) has a blind hole (121) along its thickness direction.

3. The electrode sheet according to claim 2, characterized in that, The dimension A21 of the blind hole (121) along the length direction of the electrode (100) satisfies d 50 ×s≤A21≤1000μm, the dimension A22 of the blind hole (121) along the width direction of the electrode (100) satisfies, d 50 ×s≤A22≤1000μm, where d 50 s% is the average diameter of the silicon-based active material particles, and s% is the mass percentage of the silicon-based active material in the electrode (100).

4. The electrode sheet according to claim 2, characterized in that, The blind holes (121) are provided on both sides of the tail region (120). The depth D1 of the blind hole (121) on one side along the thickness direction of the electrode (100) and the thickness D of the electrode (100) satisfy: 0.1≤D1 / D≤0.

3.

5. The electrode sheet according to claim 2, characterized in that, The dimension of the head region (110) along the length direction of the electrode (100) is L1, and the overall length of the electrode (100) is L, satisfying: 0.15≤L1 / L≤0.3; And / or, the end region (120) is connected to the beginning region (110).

6. The electrode sheet according to any one of claims 2-5, characterized in that, The beginning area (110) is provided with a plurality of through holes (111), and any two through holes (111) are spaced apart. The end area (120) is provided with a plurality of blind holes (121), and any two blind holes (121) are spaced apart. The distance between the centers of two adjacent through holes (111) along the length direction of the electrode (100) is S1, and the distance between the centers of two adjacent blind holes (121) along the length direction of the electrode (100) is S3, satisfying: S3 / S1≥1+0.05s, where s% is the mass percentage of the silicon-based active material of the electrode (100); and / or, The distance between the centers of two adjacent through holes (111) along the width direction of the electrode (100) is S2, and the distance between the centers of two adjacent blind holes (121) along the width direction of the electrode (100) is S4, satisfying: S2=S4.

7. The electrode sheet according to any one of claims 1-5, characterized in that, The beginning area (110) is provided with a plurality of through holes (111), and any two through holes (111) are spaced apart; The distance between the centers of two adjacent through holes (111) along the length direction of the electrode (100) is S1, satisfying: 0.1mm ≤ S1 ≤ 2mm; and / or, The distance between the centers of two adjacent through holes (111) along the width direction of the electrode (100) is S2, satisfying: 0.1mm ≤ S2 ≤ 2mm; and / or, The through hole (111) is a circular hole, and the diameter A1 of the through hole (111) satisfies: 80μm≤A1≤600μm.

8. The electrode sheet according to any one of claims 2-5, characterized in that, The rolled-tail area (120) is provided with a plurality of blind holes (121), and any two blind holes (121) are spaced apart; The distance between the centers of two adjacent blind holes (121) along the length direction of the electrode (100) is S3, satisfying: 0.14mm ≤ S3 ≤ 4mm; and / or, The distance between the centers of two adjacent blind holes (121) along the width direction of the electrode (100) is S4, satisfying: 0.1mm ≤ S4 ≤ 2mm; and / or, The blind hole (121) is a circular hole, and the diameter A2 of the blind hole (121) satisfies: 80μm≤A2≤600μm.

9. A winding core, characterized in that, Including the electrode as described in any one of claims 1-8.

10. A battery, characterized in that, It includes a housing and a core as described in claim 9, the core being disposed within the housing.